Effect of abscisic acid on growth and physiology of Arabica coffee seedlings under water deficit condition - Vu, Ngoc-Thang; Park, Jong-Man; Kim, Il-Soep; Tran, Anh-Tuan; Jang, Dong-Cheol (Penerbit Universiti Kebangsaan Malaysia, 2020)
In this study, the effect of abscisic acid (ABA) on growth and physiology of Arabica coffee seedlings under water deficit condition was investigated. To examine the effect of ABA concentration on growth and physiology, six ABA concentrations (0, 10, 50, 100, 150, and 200 mgL-1) were applied by spraying once a day for three days. Additionally, the effect of ABA on physiology of Arabica coffee seedlings under water deficit condition was examined by using two concentrations (50 and 100 mgL-1) compared to non-ABA (0 mgL-1). Foliar application of ABA decreased the growth traits of coffee seedlings in all the ABA concentrations. However, no statically significant difference was observed among the 0, 10, 50, and 100 mgL-1 treatments with growth traits except for the leaf area. Foliar application of ABA decreased the quantum efficiency of photosystem II (Fv/Fm) of Arabica coffee seedlings in watering condition. However, there was no significant difference between 0 (control) and 10 mgL-1 of ABA or 50 and 100 mgL-1 or 150 and 200 mgL-1 of ABA treatment with the Fv/Fm. The application of ABA enhanced drought tolerance of coffee seedlings by increasing the leaf chlorophyll content, Fv/Fm and relative water content in the leaf and reducing the relative ion leakage in the Arabica coffee seedlings. The application of ABA increased the relative water content in the soil and delayed the starting time of wilting point under water deficit condition.